2005
DOI: 10.1038/nature04032
|View full text |Cite
|
Sign up to set email alerts
|

Proteorhodopsin in the ubiquitous marine bacterium SAR11

Abstract: Proteorhodopsins are light-dependent proton pumps that are predicted to have an important role in the ecology of the oceans by supplying energy for microbial metabolism. Proteorhodopsin genes were first discovered through the cloning and sequencing of large genomic DNA fragments from seawater. They were later shown to be widely distributed, phylogenetically diverse, and active in the oceans. Proteorhodopsin genes have not been found in cultured bacteria, and on the basis of environmental sequence data, it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
322
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(337 citation statements)
references
References 21 publications
14
322
1
Order By: Relevance
“…strain MED134, PR provides energy for growth (Gómez-Consarnau et al 2007). In contrast, no growth stimulation by light was observed in the SAR11 strain HTCC1062 (Giovannoni et al 2005a). The second group of marine bacteria utilizing light was reported from the equatorial Pacific by Kolber et al (2000).…”
Section: Role Of Aerobic Anoxygenic Phototrophs In the Marine Carbon mentioning
confidence: 69%
“…strain MED134, PR provides energy for growth (Gómez-Consarnau et al 2007). In contrast, no growth stimulation by light was observed in the SAR11 strain HTCC1062 (Giovannoni et al 2005a). The second group of marine bacteria utilizing light was reported from the equatorial Pacific by Kolber et al (2000).…”
Section: Role Of Aerobic Anoxygenic Phototrophs In the Marine Carbon mentioning
confidence: 69%
“…The two subfamilies previously reported to be spectrally tuned (Béjà et al, 2001) are marked in blue and green boxes. SAR86 and SAR11 PR families, as well as few different PR representative's names from the Pacific Ocean (Béjà et al, 2001), Sargasso Sea shotgun-sequencing project (Venter et al, 2004), Mediterranean Sea bacterial artificial chromosomes (BACs) (Sabehi et al, , 2005, Pelagibacter ubique (Giovannoni et al, 2005a) and marine Archaea (Frigaard et al, 2006) are indicated to serve as orientation marks. Different groups discussed in the text are marked with gray boxes while groups in which spectral tuning is suggested are marked with an empty box.…”
Section: Resultsmentioning
confidence: 99%
“…Neighbor-joining phylogenetic tree of PR proteins from the SAR11 family. Next to each BAC (Sabehi et al, 2005), Sargasso Sea shotgun-sequencing singleton (Venter et al, 2004) or Pelagibacter ubique (Giovannoni et al, 2005a) PR sequence is a schematic representation of the surrounding PR neighboring proteins. PR sequences retrieved via PCR in this study are marked by boldface letters.…”
Section: Adaptation In Divergent Marine Proteorhodopsins G Sabehi Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…(Suzuki et al, 1997;Buchan et al, 2005). In contrast to an estimated 25% abundance of SAR11 in marine microbial communities from plasmid libraries (Giovannoni et al, 2005) and 12-37% abundance from direct counting of SAR11 using fluorescent in situ hybridization (Mary et al, 2006), Gilbert et al (2008) isolated only a single clone containing a 16S rRNA gene with homology to the SAR11 clade from a marine surface water fosmid library of 10 000 clones. It is interesting that this clone consisted largely of the 48-kb hypervariable region neighbouring the 16S rRNA gene, with a richer GC content than the GC-poor SAR11 core genome.…”
Section: Introductionmentioning
confidence: 99%